Fiber‐based light sources for biomedical applications of coherent anti‐Stokes Raman scattering microscopy. Issue 5 (6th August 2015) - Gottschall, Thomas; Meyer, Tobias; Baumgartl, Martin; Jauregui, Cesar; Schmitt, Michael; Popp, Jürgen; Limpert, Jens; Tünnermann, Andreas
<x xml:space="preserve">Abstract</x> Coherent anti‐Stokes Raman scattering (CARS) microscopy is one of the most powerful imaging techniques in the biomedical sciences for visualization of chemical composition of tissue in vivo in real time. To date, CARS imaging is employed in fundamental research only as laser sources required for CARS microscopy are large, expensive and require regular maintenance. Laser sources based on optical fibers can overcome this limitation combining highest efficiency and peak powers with an excellent spatial beam profile and thermal stability. We revise the ideal laser parameters for CARS imaging and discuss the suitability of different laser concepts for turn‐key operation required for routine application in clinics.